The Implementation of Social Media to Develop Students’ Writing Skill on Digital Marketing - Natsir, Muhammad; Suswati, Rita; Damanik, Sisila Fitriany; Pane, Isli Iriani Indiah; Lubis, Fauziah Khairani (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
Digital marketing has become a new way to exchange things, starting from information to selling things. UniversitasNegeri Medan (UNIMED) as one of the educational university tries to engage to this digital world. Since the currentfacility of multimedia laboratorybased on Computer Assisted Language learning (CALL), the implementation of e-learning has been developed. Through English for Spesific Purposes (ESP), the students learn further on e-world. The aim of this research is to find out the students’ ability in writing an advertisement using social media. This research used a development research approach (R & D) that adopts a model developed by Borg & Gall and the questionnares were analyzed by Linkert Scale formula. The research activities wasin the second semester consist of 30 english literature students carried out pre- and post-test, expert validation, and final product. The result shown: 1) social media like Instagram can be developed as the writing material; 2) students’ ability in writing using social media can be implemented in e-marketing to design an advertisement. Furthermore, it’s suggested to do more research on digital marketing to offer a wider opportunies to students in deciding the best job in the future.